Respon Pemberian KNO3 dan Pupuk Agrodyke Terhadap Hasil Tanaman Jeruk Siam (Citrus nobillis var microcarva L.) - Wayan Hendrajaya; Ni Komang Alit Astiari; Ni Putu Anom Sulistiawati (GEMA AGRO, 2019)
This study aims to determine the response of KNO3 and Agrodyke fertilizer to the yield of siam oranges and their interactions. This research is a field experiment conducted in Banjar Belancan, Belancan Village, Kintamani Subdistrict, Bangli Regency starting from January to July 2018. This study uses a Randomized Block Design (RBD) with 2 factors arranged factorially. the first factor was tried was KNO3 which consisted of 3 levels namely K0 (0 g/plant), K1 (20 g/plant) and K2 (40 g/plant, while the second factor that was tried was Agrodyke (A) fertilizer consisting of 4 levels namely A0 (0 g/plant), A1 (15 g/plant), A2 (30 g/plant) and A3 (45 g/plant), thus there are 12 combination treatments, each repeated 3 times so that 36 trees are needed Siamese plants interaction between KNO3 treatment with Agrodyke fertilizer treatment (KxA) had no significant effect (Pâ‰¥0.05) on all observed variables KNO3 treatment The highest fruit weight per tree was obtained in KNO3 treatment with a dose of 40 g / plant (K2) ie 12.70 kg increased by 50.29% when compared to the lowest yield in the treatment without KNO3, which was only 8.45 kg, the highest yield of fruit per tree was obtained in Agrodyke treatment with a dose of 30 g/plant (A2), namely 12.90 kg has increased 61.47% when compared to h the lowest acyl in treatment without Agrodyke is 7.89 kg.